Correction to: The prognostic impact of Her2 status in early triple negative breast cancer: a Turkish Oncology Group (TOG) study (Scientific Reports, (2024), 14, 1, (23556), 10.1038/s41598-024-75293-5) - Özyurt, Neslihan; Alkan, Ali; Gülbağcı, Burcu; Seyyar, Mustafa; Aşık, Esra; Şahbazlar, Mustafa; Doğan, Mutlu (Nature Research, 2025)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-024-75293-5, published online 09 October 2024 The original version of this Article contained an error in the spelling of the author Esra Aşık which was incorrectly given as Esra Aydın. The original Article has been corrected. © The Author(s) 2024.
Keywords: drug therapy; erratum; human; prevention; diagnosis